2008
DOI: 10.1097/01.tld.0000318937.39301.76
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Transcription Accuracy and Reliability in Two Languages

Abstract: Recent research documents the power of oral narrative language samples to predict reading achievement in both Spanish and English in English language learners (ELLs; J. Miller et al., 2006). To document their clinical utility, this article addresses issues of accuracy and reliability for transcription and analysis of oral narratives elicited from Spanish-English bilingual children. We first reviewed the unique considerations that must be made when transcribing narratives elicited from ELLs. To demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 6 publications
0
39
0
1
Order By: Relevance
“…All English language samples were transcribed by native English speakers, and all Spanish language samples were transcribed by native Spanish speakers. Heilmann et al (2008) found high levels of accuracy across English and Spanish transcriptions 2 The SALT database had a significantly smaller number of samples available for first grade students (N = 76); thus, we chose not to include this grade in the analysis. across four domains: utterance segmentation, main body words and morphemes, words, morphemes, and mazes, and maze placement.…”
Section: Language Sampling Proceduresmentioning
confidence: 99%
“…All English language samples were transcribed by native English speakers, and all Spanish language samples were transcribed by native Spanish speakers. Heilmann et al (2008) found high levels of accuracy across English and Spanish transcriptions 2 The SALT database had a significantly smaller number of samples available for first grade students (N = 76); thus, we chose not to include this grade in the analysis. across four domains: utterance segmentation, main body words and morphemes, words, morphemes, and mazes, and maze placement.…”
Section: Language Sampling Proceduresmentioning
confidence: 99%
“…Codes were then added for mazes, root words, and unintelligible segments, again following SALT guidelines. The second author, a Spanish-English bilingual speech-language pathologist, independently relistened to all language samples to verify transcription accuracy and modified C-unit segmentation and SALT coding; this is an established method of ensuring transcription and coding accuracy (Heilmann et al, 2008). …”
Section: Language Samplesmentioning
confidence: 99%
“…A total of 549 words or phrases were identified within the children's data set. Inter-rater reliability was acceptable at 86% (Heilmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%